Inter-seasonal Effects on Selected Maturity Parameters of DK8031 Maize Grown under Varying Irrigation and Nitrogen Levels in Embu County, Kenya - Onyari, Charles N.; Kibe, Antony M.; Mwonga, Samuel (My University, 2017)
Maize is a staple food and a source of carbohydrates to a large proportion of people in Kenya. The performance of crop plants such as maize depends on a number of factors such as climate, soil characteristics and plant species. The maturity parameters such time to tassel, milk stage, physiological maturity and biological maturity are consequently affected which in turn has an influence on crop performance. A study was carried out at University of Embu Demonstration Farm that lies at 03° 30 ′ S latitude, 37° 30 ′ E longitude, and altitude 1480 m above sea level, soils being Humic Nitisols. To evaluate the effects of seasonal weather variability on maturity parameters of DK8031 maize, a CRBD in a split plot experimental arrangement was set up in which four irrigation levels (I) and five nitrogen fertilizer rates (N) were allocated the main and subplot treatments in two seasons, respectively. The results revealed that the irrigation levels and nitrogen rates significantly (P<0.05) affected the time to reach the 50% tasseling, 50% milk stage and 50% physiological maturity, ranging from 69 to 73, 99 to 107 and 128 to 140 days after planting, respectively. In all cases, Season I (cool and less rainfall, 530.3 mm) crop took longer to reach any the three developmental stages, compared to Season II (warm and more rainfall = 605.6 mm). The time variation in reaching the developmental stages was attributed to the seasonal weather conditions. Farmers can opt to plant their maize crop in Season II to take advantage of the shorter period the crop takes to mature.
Keywords: Maize; tasseling; milk stage; physiological maturity; irrigation level; nitrogen rates; season